Measurement of intraocular pressure with applanation, dynamic contour, and air-puff tonometers: A comparative study in primary open-angle glaucoma and healthy cases - Özbilen, Kemal Turgay; Kocabora, Mehmet Selim (My University, 2020)
Objectives: This study aimed to investigate and compare the reliability of Goldmann applanation tonometer (GAT), dynamic contour (DCT), and noncontact (NCT) tonometers in intraocular pressure (IOP) measurement and the affecting parameters in healthy subjects and cases with primary open-angle glaucoma (POAG). Methods: Left eyes of 64 cases (32 males and 32 females) were selected for this prospective, controlled study. Of these cases, 33 had POAG, and 31 were selected as control. IOP measurement was performed using NCT, DCT, and GAT consecutively for each patient, and then central corneal thickness (CCT) was measured. Ocular pulse amplitude (OPA) and all values were recorded. Results: The mean age was 53.36±10 years (31–80 years), and CCT was 561±45 ?. IOP was found as 16.39±3.75 mmHg with GAT, 17.89±3.55 mmHg with DCT, and 15.76±3.49 mmHg with NCT. A significant difference was found between DCT with NCT and GAT. Whereas, a positive correlation was found between CCT with all the three methods used, with DCT as the weakest. While the correlation between all the three methods was excellent, the strongest was found to be between DCT and GAT. Thick corneas affected all the three methods, but DCT was the least affected. While DCT tends to measure higher than both GAT and NCT, this difference decreased as the corneal thickness increased. OPA was found to be 2.56±1.04 mmHg; no statistical difference was found between the groups. A correlation was found between OPA and IOP, and OPA was found to be significantly higher in women. Conclusion: DCT is minimally affected by corneal factors, especially in thin corneas, and shows excellent correlation with GAT. This new-generation digital tonometer can be used safely in glaucoma diagnosis and follow-up
Keywords: Intraocular Pressure; Ocular; Open-Angle Glaucoma; Ocular Pulse Amplitude; Pascal Dynamic Contour tonometer; Tonometry